Total hip arthroplasty using Fitmore® stem in treatment of hip osteoarthritis - 3 years folow-up - Stojiljkovic, Predrag Miroslav (Acta medicae Medianae, 2021)
Hip osteoarthritis is a chronic degenerative disease with usually manifestations after fifty years of life. The method of choice in the treatment of hip osteoarthritis in advanced stages of the disease is total hip arthroplasty. Fitmore® hip stem belongs to the short-tem which saving bone mass in the region of the greater trochanter and the distal part of the femur. In this paper we present the results of total hip arthroplasty  using  Fitmore®   stem in treatment of hip osteoarthritis.We report a series of 10 patients with osteoarthritis of hip treated by total cementless hip endoprosthesis with Fitmore® Hip Stem at the Clinic for Orthopedics and Traumatology, Clinical Center Nis. The average age of patients was 54.5 (48 - 65) years. There were 5 women and 5 men. Patients were followed for 3 years postoperatively. Functional outcome was assessed according to Harris Hip Score-u. Radiographic analysis was performed on the radiograph of the hip joint in anterior-posterior projection.In 7 patients we had exellent and in 3 patients  good functional outcome according Harris Hip Score. All patients radiological findings after 3 years shows good integration of Fitmore® stem. The 4 patients had  cortical hypertrophy of the femur.  In patients with hypertrophy of cortex, ther were no clinical manifestations. Implantation of total cementless hip joint endoprosthesis with Fitmore®  stem in the treatment of hip osteoarthritis is a good choice in the treatment of younger patients with good bone quality.
Keywords: hip osteoarthritis, total hip arthroplasty, Fitmore® Hip Stem